IN SEARCH OF EXTANT TC IN THE EARLY SOLAR SYSTEM: 98RU AND 99RU ABUNDANCES IN IRON METEORITES AND CHONDRITES - Becker H.; Walker R.J. (My University, 2003)
The short-lived 98Tc-98Ru (Half-life between 4 and ~10 Ma) and 99Tc-99Ru (Half-life 0.21 Ma) decay systems have the potential to provide important information on the relative chronology of processes that affected metal phases in the early solar system. The proof of extant 99Tc in the solar system would also tightly constrain the time interval between production of the nuclide and injection of s-process isotopes into the protosolar cloud.High-precision Ru isotopic data for group IIAB (Negrillos, Bennett County, Coahuila, Filomena, Old Woman) and IIIAB (Casas Grandes, Costilla Peak) iron meteorites, and the chondrites Allende (CV3) and Allegan (H5) indicate that the isotopic compositions of 98Ru and 99Ru in these meteorites overlap with the terrestrial values at the +/-0.8 and +/-0.3# levels (parts in 10,000), respectively. Previous reports of positive deviations of 98Ru in Negrillos and Casas Grandes likely reflect inaccurate measurements.Evaluation of processes that may fractionate Tc/Ru in solar system objects suggests that this ratio likely varied by only a factor of 2 or less. Using this constraint and solar system initial abundances of 99Tc derived from astrophysical models, evolution models for the 99Tc-99Ru system predict deviations in 99Ru of >0.3# only, if these fractionation events occurred during collapse of the molecular cloud (<10 ka). thus, positive identification of enriched 99Ru may require better than 0.1# unit resolution. Absence of resolvable 98Ru deviations indicates 98Tc/96Ru#i<2x10-5.
Keywords: TECHNETIUM; RUTHENIUM ISOTOPES; SOLAR SYSTEM; IRON METEORITES; CHONDRITES